Behçet Necatigil ve divan şiiri geleneği - Arslan, Ali (Fatih Sultan Mehmet Vakıf Üniversitesi, Sosyal Bilimler Enstitüsü, 2018)
Bu qah§mada Divan §iirinin Cumhuriyet donemi Turk §airlerinden Behqet Necatigil §iiri iizerindeki etkisi incelenerek ara§tmlml§tlr. Oncelikle Cumhuriyet donemi §airleri iqinde Behqet Necatigil'in konumu tespit edilmi§tir. Cumhuriyet donemi §airlerinin gelenege bak.J§ aqlSl ve divan §iirine yakla§lffil kar§lsmda Behqet N ecatigil 'in Divan §iirine kar§l olan tavn tespit edilmi§tir. Behqet Necatigil gelenegi ve Divan §iirini bir bilgi alam olarak gormii§ poetik yaralanma ve beslenme imkfuu bulmu§tur. Divan §iirinde kullamlan bir taklm mazmunlan ve mitolojik unsurlar1 kendi §iiri iqinde kullanarak zengin qagn§lm alan1 olu§turmu§tur. Bir taklm mazmunlan ise donii§tiirerek imge diinyasma katml§tlr. Divan §airlerine gondermeler yaparak referans alam olu§turmu§, tazmin sanatma ba§vurmu§, ayet ve hadisleri §iirine dogrudan alarak iktibas yapml§tlr. S1k s1k ba§vurdugu kelime oyunu yapmay1 ve kulland1g1 edebi sanatlardan mecaz, kinaye, te§bih, te§his, tevriye, telmih, leffii ne§r, irad-1 mesel v. b. sanatlar1 incelenip tespit edilmeye qah§llml§tlr.

In this study, Behqet Necatigil, a Turkish poet of Republican period of Divan poetry, investigated by examining the effect on poetry. First of all, the position of Behqet Necatigil in the poets ofthe Republican period was determined. Behqet Necatigil's attitude towards Divan poetry was determined in the face of the viewpoint of the poets of the Republican period on the tradition and the approach to divan poetry. Behqet Necatigil saw tradition and Divan poetry as an information field and found poetic injury and nutrition possibilities. In the Divan poetry, a number of mazmunas and mythological elements were used in their poetry to create a rich connotation area. A number of mazmunas have transformed into the world of images. He created a reference field by refering to Divan poets, resorted to the art of redemption, quoted hadiths directly by taking his poem. Metaphor, parable, comparison, diagnostic, tevriye, reference, leff-u nesr, irad-i mersel arts were studied and tried to be made from the literary arts which he frequently uses and to use the word game.
FSM Vakıf Üniversitesi, Sosyal Bilimler Enstitüsü
Keywords: Divan Şiiri; Behçet Necatigil; Mitoloji; Mazmun; İktibas; Edebi Sanatlar; Divan poetry; Mythology; Quotations; Literary arts